Youthful visions: navigating faith and the future - Dias, Patrícia (2024)
This study delves into the pivotal role of core values and beliefs in shaping the daily choices, actions, and perceptions of youth. While youth embodies promise and hope for a better future, contemporary challenges arise from irreversible past decisions. World Youth Day serves as a platform for reflection on these challenges through the lens of Catholic values. Focused on the realization of World Youth Day in Lisbon, Portugal, in 2023, this research seeks to characterize how Portuguese youth perceives their future. An online survey conducted between April and October 2022 gathered responses from 2480 individuals aged 14 to 30. The findings illuminate the religious beliefs and practices of Portuguese youth, revealing the importance of specific values and how they envision their future. The study also explores correlations between projected futures, core values, and religious faith, shedding light on the changes these young individuals desire and consider essential, as well as their perceived roles as agents of change.